(untitled) (Psychology Travelogs, 2024)
The article aims to investigation of one of the most important problem of modern society – manipulation as the technology of communicative influence to people consciousness. Manipulation by society consciousness is extremely relevant today and often is the subject for scientific discussion. Based on analysis of thematic literature main types of manipulative techniques with use various means, methods and technologies of informational and psychological actions were determined. This article reveals the peculiarities of communicative manipulations, which are growing every day and even pose a threat for informational and psychological personal safety. The major task of this article is to provide the manipulating people phenomenon and identifying of manipulation influence to interpersonal communication. Attention of the article is focused on manipulation as the technology of communicative influence and also the main approaches to the concept of the term «manipulation» are considered. It is proposed to consider the concept of «manipulation» in two aspects, that is physical (the object of influence - objects) and psychological (the object of influence - consciousness). Communicative manipulation is determined as a hidden psychological enforcement of the person or group of people affecting their emotional state, motivation, and correct thinking. Manipulation as a management specific method is used in all levels of people social interaction. As a result of theoretical analysis, the most significant interpretations of the concept of «manipulation» were characterized. Using this psychological technique, a manipulator aims to change the behavior increasing negative psychological influence. Manipulation by the people is known throughout all the history of society. Nowadays manipulation is not only very prevalent but also characterized by a variety form for its implementation. Techniques of manipulation are using by those who wish dominate to others. Manipulative actions are becoming more pronounced and sometimes even dangerous for people.